Microwave Assisted Facile Synthesis of Zinc-Oxide-Activated Carbon Nanocomposite for Photo-Fenton Degradation of Phenol - Ojoro, Zainab Eniola (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
This work describes simultaneous removal of phenol and photocatalytic experiment to degrade phenol from aqueous solution. Microwave assisted facile synthesis of ZnO-activated carbon nanocomposite for phenol removal employs the use of activated carbon synthesized from waste palm seeds in an easily achievable, cheap and fast method to degrade and remove phenol by depositing ZnO on the activated carbon to produce a rich nanocomposite of Ac-ZnO for subsequent adsorption of phenol onto the activated carbon’s surface, followed by photocatalytic degradation of phenol. Further characterization of the nanocomposite produced was achieved using FTIR, pH point of zero charge and SEM analysis. The following studies were optimized; effect of pH, concentration, adsorbent dosage, effect of contact time and photocatalytic experiment. Based on this experiment, phenol adsorption followed kinetics of the pseudo-first order , maximum phenol adsorption of 39.62mg/g, was recorded at pH 5.0, 0.2g of adsorbent, 400mg/L of phenol under sunlight, this shows an improvement in catalytic activity of phenol aided by sunlight irradiation and introduction of •OH radicals gotten from of H202 to oxidize and degrade phenol. Keywords: Activated Carbon, adsorption, Palm seeds, photocatalysis, phenol.

ÖZ : Bu çalışma, sulu bir çözeltiden fenolün giderimi ile aynı anda fotokatalitik yöntemle fenolün parçalanmasını tanımlamaktadır. Mikrodalga destekli olarak ZnO-Aktif karbon nanokompozitik olaylıkla sentezlenerek fenol gideriminde kullanılmıştır. Atık palmiye tohumundan elde edilmiş aktif karbonun ZnO ile zenginleştirilmiş nanokompoziti olan Ac-ZnO, sırasıyla aktif karbon yüzeyinde adsorpsiyon ardından fotokatalitik parçalanma ile fenolü kolay, ucuz ve hızlı bir yöntemle giderimiştir. FTIR, pH noktası Zero Charge ve SEM analizleri kullanılarak üretilen nanokompozitin ileri karakterizasyonu elde edilmiştir. Aşağıdaki çalışmalar optimize edilmiştir; pH, konsantrasyon, adsorban dozajı, temas süresi ve fotokatalitik deney etkisi etkisi.Bu deneye göre, fenol adsorpsiyonun yalancı birinci mertebe kinetiğine uymaktadır ve 400 mg/L fenole karşın pH 5.0 da 0.2 g adsorbent, güneşışığıaltında H2O2 oksidasyonu ile oluşan .OH radikallerinin fenolü parçalama etkisiyle 39.62 mg/g değerindeki maksimum fenol adsorpsiyonuna ulaşmıştır. Anahtar Kelimeler: Aktif Karbon, adsorpsiyon, Palmiye tohumu, fotokataliz, fenol.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2015. Co-Supervisor: Assist. Prof. Dr. Ozan Hayrettin Gülcan, Supervisor: Assoc. Prof. Dr. Mustafa Gazi.
Keywords: Chemistry; Activated Carbon; adsorption; Palm seeds; photocatalysis; phenol